Coverage and factors associated with completion of continuum of care for maternal health in sub-Saharan Africa: a multicountry analysis - Adugnaw Zeleke Alem; Kegnie Shitu; Tesfa Sewunet Alamneh (BMC, 2022)
Abstract Background Many maternal and neonatal deaths are largely preventable by expanding the continuum of care (at least four antenatal visits, skilled birth attendance and postnatal care). Even though ensuring the Continuum of Care (CoC) has advantages over separate services, evidence from the globe suggests that completion of the CoC for maternal health is very low. From our search of the literature, there is limited evidence on the completion of the entire CoC and its associated factors in sub-Saharan Africa (sSA). Therefore, this study aimed to assess coverage and associated factors of completion of the CoC for maternal health in sSA. Methods Data for the study were drawn from a recent nationally representative survey of 32 Demographic and Health Surveys (DHS). A total weighted sample of 225,135 women of reproductive-age, who gave birth in the two preceding years were included. Due to the hierarchical nature of DHS data, a multilevel logistic regression model was applied to investigate individual and community-level factors that may influence completion of CoC. Adjusted Odds Ratios (aORs) with 95% Confidence Interval (CI) were reported and variables with 95% CI not including 1 were considered as significant factors of the completion of CoC. Results Only, 56,172 (25.0%; 95% CI, 20.5%, 29.4%) of the women in sSA utilized the CoC for maternal health which varied from 11,908 (17.9.0%) in East Africa to 7,418 (51.5% in Southern Africa. Factors associated with higher odds of CoC were women aged 24-34 years (aOR 1.22, 95% CI: 1.17, 1.25), aged ≥ 35 years (aOR 1.40, 95% CI: 1.35, 1.47), attending primary education (aOR 1.44, 95% CI: 1.41, 1.49), secondary education (aOR 1.95, 95% CI: 1.89, 2.03), higher education (aOR 2.15, 95% CI: 2.01, 2.25), having mass media exposure (aOR 1.35, 95% CI: 1.28, 1.39), women from female-headed households (aOR 1.18, 95% CI: 1.15, 1.21) and women from communities with high maternal education (aOR 1.12, 95% CI: 1.09, 1.16). However, perceiving distance from the health facility as a big problem (aOR 0.88, 95% CI: 0.85, 0.91), residing in rural areas (aOR 0.78, 95% CI: 0.75, 0.81), delayed ANC initiation (aOR 0.43, 95% CI: 0.41, 0.47) and unintended pregnancy (aOR 0.87, 95% CI: 0.84, 0.91) were associated with lower odds of CoC. Conclusion This study showed a low proportion of women, who utilized the CoC in sSA. Both individual and community-level factors were associated with CoC completion rates among women in sSA. Therefore, policymakers in sSA must consider both individual and community-level factors and undertake multi-sectorial approaches to address barriers of CoC at different levels.